14 kyr of atmospheric mineral dust deposition in north-eastern China: A record of palaeoclimatic and palaeoenvironmental changes in the Chinese dust source regions. (April 2020) - Pratte, Steve; Bao, Kunshan; Sapkota, Atindra; Zhang, Wenfang; Shen, Ji; Le Roux, Gaël; De Vleeschouwer, François
A multi-proxy record of Holocene and late-Pleistocene aeolian mineral dust is reconstructed using a combination of geochemical (trace elements), mineralogical and grain-size analyses on cores from the Hani peatland in north-eastern (NE) China. The dust record displays a sharp increase in dust deposition during the late Holocene in comparison to the rest of the Holocene. This trend is in line with climatic records from the Chinese dust source regions and their downwind areas, which generally show an increase in aridity and aeolian activity during the late Holocene. The larger part of the Chinese dust source regions experienced a gradual increase in effective moisture and vegetation cover reaching maxima during the middle Holocene (6.0–8.0 kyr cal. BP) co-occurring with the minima in dust deposition in Hani. These changes in the dust source regions are likely to have been modulated by the variations in the East Asian summer monsoon (EASM), which is the principal mechanism controlling climate in the region. The intensified EASM during the middle Holocene is also likely to have resulted in a sediment recharge at the margin of the Chinese drylands providing additional material and enhancing the atmospheric dust load after the late-Holocene aridification of the region. Combined together, these changes promoted a remobilization of dust sources increasing the amount of material available for transport by the East Asian winter monsoon (EAWM) and the Westerlies. Human activities might also have played a role in the increased dust emissions during the late Holocene, but further research is needed to assess the extent of those impacts at a regional level.